Pengaruh Fasilitas Kantor dan Motivasi terhadap Kinerja Pegawai pada Kantor Kecamatan Rangkasbitung - Suci Ramanda Fitriani; Tarwijo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study was to determine the effect of Office Facilities and Motivation on Employee Performance at the Rangkasbitung sub-district office both partially and simultaneously. This research method is a quantitative descriptive type using a questionnaire instrument. The population and sample of this researcher amounted to 53 respondents and used saturated sampling techniques. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. Based on the results of the t test tester for the Office Facility variable (X1), the tcount value is 2.921> from the t table 1.675 with a significance level of 0.05> 0.00, so there is an influence between Office Facilities (X1) on Performance (Y). The results of the t test for the Motivation variable (X2) obtained a tcount value of 1.164 < t table 1.675, so there is no influence between Motivation (X2) on Performance (Y). Simultaneously with the F test there is a positive and significant influence between office facilities and motivation on performance at the Rangkasbitung District Office which can be seen from the value obtained, namely Fcount of 10.290> 2.40 Ftable with a significance level of 0.05.